2020
DOI: 10.1016/j.heliyon.2020.e04932
|View full text |Cite
|
Sign up to set email alerts
|

Changes in splenic uptake pattern associated with X-ray irradiation

Abstract: Purpose To evaluate the splenic uptake function after irradiation with high-energy X-rays. Materials and methods Fourteen male Wistar rats were distributed into three groups. Group 1 (n = 6) – control, non-irradiated; Group 2 (n = 4) – animals that were irradiated and studied 24 h after irradiation; and Group 3 (n = 4) – animals that were irradiated and studied 48 h after irradiation. The animals were irradiated with 8 Gy X-rays in the abdominal region. According with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The splenic macrophages containing carbon pigments were uniformly distributed in the splenic parenchyma of the control group. However, in the irradiated groups B and C, they were located mainly in the marginal zone around white pulps, as previously described 8 ( Fig. 3 ).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The splenic macrophages containing carbon pigments were uniformly distributed in the splenic parenchyma of the control group. However, in the irradiated groups B and C, they were located mainly in the marginal zone around white pulps, as previously described 8 ( Fig. 3 ).…”
Section: Resultssupporting
confidence: 84%
“…This study aimed to verify the megavoltage radiotherapy effects on RES, based on the previous results, which have shown that the concentration of the colloidal uptake activity in the splenic marginal zone after irradiation with a single dose of high-energy XR 8 , as well as a reduction of the hepatic uptake of a technetium-phytate solution injected in the animals 9 . The reduction of the hepatic uptake activity might be related with radiation-induced damage to the liver parenchyma that was histologically investigated in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the mass and morphology of these organs may serve as additional markers for assessing the impact of proton irradiation on the hematopoietic and immune systems. Currently, there is a lack of research on lymphoid organs, and existing literature focuses on the development of immunosuppression in various compartments of the immune system during high-dose total X-ray irradiation in the short-term period after irradiation [61][62][63]. These changes are often associated with a sharp increase in cellular destruction, leading to loss of lymphocytes, and complete inhibition of cellular mitotic activity and differentiation [64].…”
Section: Discussionmentioning
confidence: 99%